A case series on the use of steroids and mycophenolate mofetil in idiopathic and heritable pulmonary veno-occlusive disease: is there a role for immunosuppression?. Issue 6 (24th June 2021) - Bergbaum, Carmel; Samaranayake, Chinthaka B.; Pitcher, Alex; Weingart, Emma; Semple, Thomas; Kokosi, Maria; Wells, Athol U.; Montani, David; Dimopoulos, Konstantinos; McCabe, Colm; Kempny, Aleksander; Harries, Carl; et al.
Pulmonary veno-occlusive disease (PVOD) is classified into idiopathic PVOD, heritable PVOD, and PVOD associated with other conditions: most often connective tissue disease (CTD) and sarcoidosis. In patients with PVOD and a CTD, immunosuppressive therapies can improve symptoms, gas transfer, imaging and haemodynamics [1, 2]. Despite evidence for inflammation in PVOD pathophysiology [3, 4], including capillary immune complex and complement deposition [5], the role for immunosuppression in idiopathic or heritable forms of PVOD is uncertain. We present three patients with heritable and idiopathic PVOD who received immunosuppression for suspected immune dysregulation. Patients with heritable and idiopathic PVOD have few therapeutic options. On suspicion of immune dysregulation, methylprednisolone or oral prednisolone then mycophenolate mofetil was trialled in three cases, with resulting clinical improvement/stability. https://bit.ly/376mwR9